Key Range Locking Strategies for Improved Concurrency - Lomet, David (Morgan Kaufmann Publishers, 1993)
"Phantoms" are records inserted into a concurrently selected set of records specified by a predicate such that the selection does not see a transaction consistent result. The usual locking strategy is to lock only existing records. However, records that satisfy the selection predicate must be locked even when they are not present in the database to prevent their insertion. One way to cope with phantoms is through range locking, a limited form of predicate locking. We investigate lock modes for ranges and describe new lock modes that greatly increase concurrency. We explore locking strategies involving range, key, and record resources that permit trade-offs between concurrency and lock overhead.